Elements of Tragedy in The Writings of Krishan Chander - Jafar, Syed Nadeem (Makhz (Research Journal), 2025)
This paper explores the fictional universe of Krishan Chander, a prominent voice in modern South Asian literature, whose work is marked by exceptional versatility and emotional resonance. Focusing on seminal novels such as Shikast, Ghadar, Barf Ke Phool, Ek Aurat Hazaar Diwaane, and Aasmaan Roshan Hai, the study delves into the recurring themes of defeat, love, social alienation, and moral conflict. Through a critical examination of narrative structures and thematic depth, this research highlights how Chander’s fiction not only foregrounds the anguish of the common man but also critiques the deep-rooted social evils plaguing society. Central to his work are depictions of historical trauma, personal grief, and the disruption of traditional values, all set against the backdrop of class struggle between the bourgeoisie and the proletariat. With a tone of empathy and sharp social commentary, Chander’s narratives offer a stark reflection on human suffering and tragedy, positioning his literature as a profound lens through which the fractured realities of modern South Asia can be understood.